Evaluation of antimicrobial activity of orange peel extract against oral biofilm forming organisms: an in vitro microbial study and scanning electron microscopic assessment - Mankar, Chetana Dilip; Shah, Mona Udayan; Doshi, Yogesh Sharad; Bajaj, Monika; Kevadia, Vidhi; Vinod, Roshini (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To evaluate in vitro antimicrobial activity of orange peel extract, 0.2% chlorhexidine (CHX) and saline against dental biofilm-forming bacteria and their effect on plaque structure under SEM. Methods: Present study included 3 groups; Group A: Orange peel extract; Group B: 0.2% CHX and Group C: Saline. MIC of each group was determined by broth and well diffusion method. Reference strains of Porphyromonas gingivalis (P.g.), Prevotella intermedia (P.i.) and Aggregatibacter actinomycetemcomitans (A.a.) were selected as being colonizers in dental biofilm. For SEM analysis, plaque retained orthodontic e-chains were subjected to each group for 60s and studied under SEM. Results: The MIC of Group A by broth diffusion method is 66.66 µg/ml for P. intermedia, 75 µg/ml for P. gingivalis and 33.33 µg/ml for A.a. MIC of Group B was 14.58 µg/ml for P.i., 7.29 µg/ml for P.g. and 20.83 µg/ml for A.a. MIC of Group C was 83.33 µg/ml for A.a. while P.i. and P.g. showed resistance to Group C. The determination of MIC by well diffusion showed increase in clear zone diameter with increasing concentrations. Greater zone of inhibition was seen in Group B with statistical significance for all 3 microorganisms. Morphologic changes in the SEM study showed maximum change in the surface characteristics and loss of adhesion of the clusters of microorganisms subjected to Group B. Conclusions: CHX and orange peel extract exhibited notable anti-microbial activity against biofilm organisms, but at varying concentrations. The plaque samples subjected to orange peel extract showed slightly shrunken and coarse form indicating its ability to disrupt the plaque biofilm.